Intragranular replacement of chlorapatite by hydroxy-fluor-apatite during metasomatism - Engvik, A.; Golla-Schindler, U.; Berndt, J.; Austrheim, H.; Putnis, Andrew (Elsevier BV, 2009)
The pseudomorphic replacement of chlorapatite by hydroxy-fluor-apatite is associated with metasomatism of the Ødegården metagabbro (Bamble, south Norway). Primary fluor-chlorapatite in the protolith gabbro is non-porous and homogenous in composition with F-content of up to 3.5 wt% and Cl-content up to 2 wt.%. Metasomatism transforms apatite during multi-stage replacement reactions: I) Magmatic apatite was transformed to chlorapatite with Cl-content of up to 6.8 wt.% during scapolitisation. II) A secondary pseudomorphic replacement reaction which transforms chlorapatite to porous hydroxy-fluor-apatite with only minor Cl is related to albitisation. Laser ablation inductively coupled mass spectrometry (LA ICPMS) data from the primary fluor-chlorapatite shows in general a high content of Sr, Y, REE and Th. Chlor- and hydroxy-fluor-apatite show depletion in Co, Ni, Sr, Cd, Pb, Th and U, and enrichment in V and Ba, relative to the primary apatite. The replacement interface of chlorapatite to hydroxy-fluor-apatite is studied by energy-filtered transmission electron microscopy (TEM). The interface is sharp on a nano-scale, and the crystallographic orientation of the apatite is preserved. These observations, together with the porosity development in the hydroxy-fluor-apatite suggest that the replacement mechanism is by interface-coupled dissolution-reprecipitation. © 2009 Elsevier B.V. All rights reserved.